Addition of cellulose nanofibers extracted from rice straw to urea formaldehyde resin; effect on the adhesive characteristics and medium density fiberboard properties. (June 2020) - Moslemi, Amin; Zolfagharlou koohi, Mohsen; Behzad, Tayebeh; Pizzi, Antonio
Abstract: In this research cellulose nanofibers (CNF) were successfully extracted from rice straw through a chemomechanical method and then mixed with urea-formaldehyde (UF) adhesive for the production of medium density fiberboard (MDF). The industrial grade liquid urea-formaldehyde (UF) resin with formaldehyde: urea molar ratio of 1.15 was modified by adding 0.5, 1.5 and 2 wt % of nanofibrillated cellulose (CNF) based on UF resin solids. The morphology, gel time, viscosity, and the non-volatile solid content of the modified UF adhesive were investigated. Formaldehyde emission and some mechanical properties modulus of rupture (MOR), modulus of elasticity (MOE) and internal bond strength (IB)) of the resulting MDF panels were measured. Solids content and viscosity of the UF adhesive decreased while gel time increased by mixing CNF with the resin. The formaldehyde emission of the panels made with UF containing CNF was lower than that of the panels made from neat UF while MOR, MOE and IB values increased by increasing the CNF content in the panels.